INNOVATIVE RECIPROCITY IN INDIAN AND WESTERN MUSIC: भारतीय और पाश्चात्य संगीत में नवाचार विषयक पारस्परिकता - Dubey, Sasikala (International Journal of Research -GRANTHAALAYAH, 2015)
At present, increasing steps of innovation are being reflected in almost every field globally. Innovative experiments are being done in the field of music, due to which various concepts related to music are giving a living momentum. There was also a time when the distinction between Indian and Western music was said to be that the listeners of Indian music shook the heads of the listeners while the westerners heard the feet of the listeners. The same belief is still prevalent among the well-known siblings of music. But from the point of view of joint creativity, it gets its own opinion. The innovations in music have also knocked on the minds of traditional listeners, consequently, innovation has awakened the reciprocal sensation of the mutual audience of music towards the modern form of music. वर्तमान समय में वैश्विक स्तर पर प्रायः हर क्षेत्र में नवाचार के बढ़ते कदम परिलक्षित हो रहे हैं। संगीत के क्षेत्र में नवाचार को लेकर नवीन प्रयोग हो रहे हैं, जिससे संगीत विषयक विभिन्न धारणाओं को जीवन्त गति मिल रही है। एक समय ऐसा भी था कि जब भारतीय और पाश्चात्य संगीत के मध्य भेद को लेकर कहा जाता था कि भारतीय संगीत को सुनने वाले श्रोताओं के सिर हिला करते हैं जबकि पाश्चात्य संगीत को सुनने वालों के पैर हिला करते हैं। संगीत के पारखी सुधीजनों के बीच आज भी यही मान्यता स्थिर है। लेकिन प्रयोग की दृष्टि से संयुक्त सृजनात्मकता अपनी बात को मनवा ही लेती है। संगीत में आये नवाचार ने भी पारम्परिक श्रोताओं के मस्तिष्क पर दस्तकें दी हैं, फलस्वरूप नवाचार के कारण संगीत के आधुनिक स्वरूप के प्रति भी संगीत के पारस्परिक श्रोताओं का रागात्मक संवेदन जागा है।99